1-Chloro-4-[2-(4-chlorophenyl)ethyl]benzene and its bromo analogue: crystal structure, Hirshfeld surface analysis and computational chemistry - Jotani, Mukesh M.; Lee, See Mun *; Lo, Kong Mun *; Tiekink, Edward R. T. * (International Union of Crystallographic, 2019)
The crystal and molecular structures of C14H12Cl2, (I), and C14H12Br2, (II), are described. The asymmetric unit of (I) comprises two independent molecules, A and B, each disposed about a centre of inversion. Each molecule approximates mirror symmetry [the Cb—Cb—Ce—Ce torsion angles = 83.46 (19) and 95.17 (17) for A, and 83.7 (2) and 94.75 (19) for B; b = benzene and e = ethylene]. By contrast, the molecule in (II) is twisted, as seen in the dihedral angle of 59.29 (11) between the benzene rings cf. 0 in (I). The molecular packing of (I) features benzene-C—H...π(benzene) and Cl...Cl contacts that lead to an open three-dimensional (3D) architecture that enables twofold 3D–3D interpenetration. The presence of benzene-C—H...π(benzene) and Br...Br contacts in the crystal of (II) consolidate the 3D architecture. The analysis of the calculated Hirshfeld surfaces confirm the influence of the benzene-C—H...π(benzene) and X...X contacts on the molecular packing and show that, to a first approximation, H...H, C...H/H...C and C...X/X...C contacts dominate the packing, each contributing about 30% to the overall surface in each of (I) and (II). The analysis also clearly differentiates between the A and B molecules of (I).